Retrieving E-learning document using encrypted semantic words - Farah Amer; Qasim Mohammed Hussein; Mohammed Sahib Mahdi Altaei (Journal of Madenat Alelem University College, 2022)
The process of retrieving document images in digital media depending on their content is difficult, especially when the number of images is very large. Therefore, there is a need to use an automated computer system to retrieve the documents based on semantic words. This paper presents an automation computer system that uses to retrieve documents images based on semantic words. Semantic words are chosen depending on the content of the document. To keep the security of the document semantic words and prevent unauthorized persons to access these documents, they are encrypted along with the document issue number using hash function and store them in index file. The importance of this work lies in the possibility of using it in the institutions archive departments to retrieve digital documents based on their content instead of their number. The implementation of this system result shows that this system can retrieve the stored documents with high accuracy and short time in easy manner.